Diaphragm-free lithium ion battery
By forming a ceramic coating with a specific particle size distribution on the electrodes of the lithium-ion battery, the safety hazards and limited cycle life of the battery in the case of short circuit or thermal runaway are solved, and higher safety performance and cycle life are achieved.
Patent Information
- Application Number
- CN202280099294.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-19
- Filing Date
- 2022-12-16
- Publication Date
- 2025-03-28
AI Technical Summary
Existing lithium-ion batteries are prone to safety accidents when short circuit or thermal runaway, and the aging of the diaphragm causes an increase in internal leakage current, limiting the battery's cycle life.
A ceramic coating with a specific ceramic powder particle size distribution is formed on the electrode to replace the traditional separator and improve the safety performance and cycle life of the battery.
The use of ceramic coatings can improve the safety performance of the battery without a membrane, extend cycle life, and increase volume specific energy.
Smart Images

Figure CN119731866A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of batteries, and in particular to a lithium ion battery without a separator. Background Art
[0002] With the advancement of information, materials and energy technology, lithium-ion batteries have become a hot topic in the research of new power technology due to their high specific energy, long cycle life, no memory effect, safety and reliability, and rapid charge and discharge. In addition to being widely used in mobile phones, laptops and other digital electronic products that we are familiar with every day, the development of electric vehicles will also drive greater demand for lithium-ion batteries, and they have also been used in aerospace, navigation, artificial satellites, small medical, military communication equipment and other fields, gradually replacing traditional batteries.
[0003] Lithium-ion batteries usually include four parts: shell, electrode, diaphragm and electrolyte. The diaphragm refers to the polymer diaphragm between the positive and negative electrodes of lithium-ion batteries. It is the most critical part of lithium-ion batteries and has a direct impact on battery safety and cost. Its main functions are: isolating the positive and negative electrodes and preventing electrons in the battery from passing freely; allowing lithium ions in the electrolyte to pass freely between the positive and negative electrodes. The lithium ion conductivity is directly related to the overall performance of lithium-ion batteries. The function of the battery diaphragm to isolate the positive and negative electrodes enables the battery to limit the increase in current when it is overcharged or the temperature rises, preventing the battery from short-circuiting and causing explosions, and playing a role in safety protection for battery users and equipment. Usually, the material of the battery diaphragm is an organic polymer material. These materials are prone to heating up in the case of battery short-circuiting or other abnormal conditions, causing the organic material to melt or even carbonize, which ultimately causes the positive and negative electrodes to contact and short-circuit or even explode. In addition, in order to limit the passage of electrons inside the lithium-ion battery, the diaphragm will increase the internal resistance of the lithium-ion battery, and as the diaphragm ages, the internal leakage current of the lithium-ion battery will also increase significantly, resulting in a limited cycle life of the lithium-ion battery.
[0004] In addition, tab-free lithium-ion batteries have many advantages such as low internal impedance, simple structure, and easy processing, and have broad application prospects. However, due to the low impedance and the fact that lithium-ion batteries without tab welding have a large short-circuit current when an internal short circuit occurs, they are prone to thermal runaway and are more likely to cause safety accidents.
[0005] Based on this, it is necessary to provide a lithium-ion battery without a separator to at least partially solve the above problems. Summary of the invention
[0006] The object of the present invention is to provide a lithium-ion battery without a diaphragm. Among them, by forming a ceramic coating with a specific ceramic powder particle size distribution on the electrode, the battery diaphragm in the usual sense can be replaced, and the ceramic coating on the electrode can replace the battery diaphragm in the usual sense. The electrode with a ceramic coating can be directly combined into a battery without the presence of a diaphragm, preventing the melting of the diaphragm under conditions such as short circuit and thermal failure of the battery, resulting in a direct short circuit between the positive and negative electrodes and causing more serious safety hazards, thereby increasing the safety performance of the battery. In addition, by using an electrode coating instead of a battery diaphragm, the cycle life and thermal stability of the lithium-ion battery can be improved. By reducing the thickness of the ceramic coating, the volume specific energy of the battery can be increased. Furthermore, on the basis of ensuring safety performance, it is more feasible to adopt a design without pole ears for lithium-ion batteries.
[0007] In one aspect of the present invention, there is provided an electrode ceramic coating, wherein the ceramic coating comprises ceramic powder and a binder, wherein the particle size of the ceramic powder satisfies D 50 It is 0.05 μm to 0.6 μm, preferably 0.07 μm to 0.4 μm, and more preferably 0.09 μm.
[0008] In one embodiment, the ceramic powder material is selected from one or more of boehmite, alumina, silica, zirconia, zeolite, magnesium oxide, titanium oxide and barium titanate, preferably boehmite and alumina, and more preferably boehmite.
[0009] In one embodiment, the binder is selected from one or more of PVDF, CMC and SBR, preferably PVDF.
[0010] In one embodiment, the mass ratio of ceramic powder to binder in the ceramic coating is (80-95):(5-20), preferably (80-90):(10-20), and more preferably 85:15.
[0011] In one embodiment, the pore volume of the ceramic coating is 280 uL / mL to 320 uL / mL, preferably 289 uL / mL to 316 uL / mL, and more preferably 315.7 uL / mL.
[0012] In one embodiment, the ceramic coating further comprises an additive, and the additive is selected from one or both of PE and PP.
[0013] In one embodiment, the ceramic coating is obtained by coating a ceramic slurry on the surface of the electrode to form a coating layer, and drying the coating layer.
[0014] Another aspect of the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a shell, wherein the positive electrode comprises a positive electrode collector and a positive electrode active material coated on the positive electrode collector, and the negative electrode comprises a negative electrode collector and a negative electrode active material coated on the negative electrode collector; wherein the positive electrode and the negative electrode are opposite to each other, and at least one surface of the positive electrode and the negative electrode opposite to each other has the electrode ceramic coating as described above.
[0015] In one embodiment, the positive electrode active material is one or more of lithium nickel cobalt manganese oxide (NCM), lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide (LMO), lithium nickel cobalt aluminum oxide and lithium iron phosphate, preferably lithium nickel cobalt manganese oxide (NCM); the positive electrode current collector is aluminum foil.
[0016] In one embodiment, the negative electrode active material is one or more of graphite (C), soft carbon, hard carbon, silicon-carbon composite, elemental silicon and SiOx, preferably graphite (C); and the negative electrode current collector is copper foil.
[0017] In one embodiment, the positive electrode and / or negative electrode further comprises a conductive agent, which may be selected from one or more of conductive carbon black, superconducting carbon black (SP), conductive carbon nanotubes, conductive carbon fibers and graphite-based conductive agents, preferably conductive carbon black, and more preferably superconducting carbon black (SP).
[0018] In one embodiment, the electrolyte is an organic electrolyte, a non-aqueous electrolyte, an organic solid electrolyte, or an inorganic solid electrolyte.
[0019] In one embodiment, the lithium ion battery does not include a separator.
[0020] In one embodiment, the lithium-ion battery does not include tabs.
[0021] In one embodiment, the compaction density of the positive electrode active material is 2.5 g / cc to 4.0 g / cc, preferably 3.0 g / cc to 3.5 g / cc, and more preferably 3.4 g / cc.
[0022] In one embodiment, the compaction density of the negative electrode active material is 0.5 g / cc to 2.0 g / cc, preferably 1.0 g / cc to 1.5 g / cc, and more preferably 1.4 g / cc.
[0023] Another aspect of the present invention provides a use of an electrode ceramic coating for extending the cycle life of a lithium-ion battery.
[0024] Another aspect of the present invention provides a use of an electrode ceramic coating for reducing the average capacity (Ah) decay of a lithium-ion battery after multiple cycles.
[0025] Another aspect of the present invention provides a use of an electrode ceramic coating for maintaining an average capacity rate (%) of a lithium-ion battery after multiple cycles.
[0026] In one embodiment, the cycle number of the lithium ion battery is ≥400, preferably ≥500, and more preferably ≥600.
[0027] In one embodiment, when the number of cycles of the lithium-ion battery is ≥400, preferably ≥500, and more preferably ≥600, the average capacity rate (%) remains ≥70%, preferably ≥75%, and more preferably ≥80%.
[0028] Another aspect of the present invention provides a use of an electrode ceramic coating for improving the high-temperature thermal stability of a lithium-ion battery.
[0029] In one embodiment, the elevated temperature is 130° C. or higher.
[0030] Another aspect of the present invention provides a use of an electrode ceramic coating for reducing the contact angle of an electrode surface of a lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is the contact angle of different electrode surfaces;
[0032] Figure 2 The charge and discharge curves of the full battery containing ceramic coating and the full battery containing separator;
[0033] Figure 3 Cycle life curves of full cells with ceramic coating and full cells with separator (Ah, +6C / -6C);
[0034] Figure 4 Cycle life curves of full cells with ceramic coating and full cells with separator (%, +6C / -6C);
[0035] Figure 5 Cycle life curves of full cells with ceramic coating and full cells with separator (Ah, +1C / -1C);
[0036] Figure 6 Cycle life curves of full cells with ceramic coating and full cells with separator (%, +1C / -1C);
[0037] Figure 7 Heating test curves of a full cell with a ceramic coating and a full cell with a separator. DETAILED DESCRIPTION
[0038] Now, with reference to the accompanying drawings, the specific embodiments of the present invention are described in detail. What is described here is only the preferred embodiment of the present invention, and those skilled in the art can think of other ways to implement the present invention based on the preferred embodiment, and the other ways also fall within the scope of the present invention.
[0039] The lithium-ion battery comprises a housing, a positive electrode, a negative electrode and an electrolyte contained in the housing, wherein the positive electrode and the negative electrode are opposite to each other, and at least one surface of the positive electrode and the negative electrode opposite to each other has a ceramic coating. The positive electrode, the negative electrode and the ceramic coating formed on at least one surface of the positive electrode and the negative electrode opposite to each other can be combined into an electrode assembly. In addition, the lithium-ion battery further comprises a cap assembly for sealing the housing.
[0040] The positive electrode is, for example, in sheet form. The positive electrode may include, for example, a positive electrode current collector and a positive electrode material. The positive electrode current collector may, for example, have a thickness of 5 μm-50 μm. The interval ranges defined in the present invention all include endpoint values. The current collector is a chemically inactive electron high conductor used to continuously flow current through the electrode during discharge or charge. The current collector may be in the shape of a foil, a plate, a mesh, etc., and there is no particular limitation as long as the shape corresponds to the purpose. Preferably, the current collector is preferably in the shape of a foil. Examples of the current collector may be aluminum foil, aluminum mesh, perforated aluminum sheet, aluminum extended sheet, stainless steel foil, stainless steel mesh, perforated stainless steel sheet, stainless steel extended sheet, extended nickel, nickel non-woven fabric, copper foil, copper mesh, perforated copper sheet, copper extended sheet, titanium foil, titanium mesh, carbon non-woven fabric, carbon woven fabric, etc. Preferably, the current collector is aluminum foil.
[0041] The positive electrode material is formed on the surface of the positive electrode current collector. The positive electrode material may be formed only on one side of the positive electrode current collector. The positive electrode material may also be formed on both the front and back sides of the positive electrode current collector. The positive electrode material may have a thickness of, for example, 10 μm to 200 μm.
[0042] The positive electrode material may contain, for example, a positive electrode active material. The positive electrode material may consist essentially of only a positive electrode active material. The positive electrode material may contain optional components. The positive electrode active material may contain, for example, at least one selected from lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide (LMO), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide, and lithium iron phosphate.
[0043] In addition to the positive electrode active material, the positive electrode material may further include a conductive agent. The conductive agent may include optional ingredients. The conductive agent may be selected from one or more of conductive carbon black, superconducting carbon black (SP), conductive carbon nanotubes, conductive carbon fibers and graphite-based conductive agents. Preferably, the conductive agent is conductive carbon black. More preferably, the conductive agent is SP. Based on 100 parts by weight of the positive electrode material, the amount of the conductive agent may be, for example, 0.1 parts by weight to 10 parts by weight, preferably 3 parts by weight.
[0044] The positive electrode material may also include a binder. The binder binds the solids to each other. The binder may include optional ingredients. Examples of the binder are polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polybenzimidazole, polyimide, polyvinyl acetate, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl methylcellulose, regenerated cellulose, polyvinyl pyrrolidone, polyethylene, polypropylene, polystyrene, polymethyl methacrylate, polyaniline, acrylonitrile-butadiene-styrene copolymer, phenolic resin, epoxy resin, polyethylene terephthalate, polytetrafluoroethylene, polyphenylene sulfide, polyamide-imide, polyetherimide, polyethylene sulfone, polyacetal, polyphenylene oxide, polybutylene terephthalate, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, fluorocarbon rubber and various copolymers, preferably one or more of PVDF, CMC and SBR. As a preferred, non-limiting example, the binder is PVDF. The amount of the binder blended may be, for example, 0.1 to 10 parts by weight, preferably 1 part by weight, based on 100 parts by weight of the positive electrode material.
[0045] In addition, the positive electrode material may also contain other additives, such as lithium carbonate (Li2CO3).
[0046] In a preferred embodiment, the positive electrode includes a positive electrode current collector made of aluminum foil and a positive electrode active material layer, wherein the positive electrode active material layer contains a positive electrode active material coated on both surfaces of the positive electrode current collector as a main component, and the positive electrode active material can be selected from one or more of lithium cobalt oxide, lithium nickel oxide, LMO, NCM, lithium nickel cobalt aluminum oxide and lithium iron phosphate. The positive electrode uncoated portion is formed at both ends of the positive electrode current collector, respectively. The positive electrode uncoated portion is an area where the positive electrode active material layer is not formed on one or both surfaces of the positive electrode. The positive electrode tab is equipped on the positive electrode uncoated portion. An insulating tape is wound around a portion of the positive electrode tab extending out of the electrode assembly to prevent short circuit. The positive electrode tab is electrically connected to the cap assembly.
[0047] In a further preferred embodiment, the positive electrode does not include a positive electrode tab, but instead uses an uncoated portion of the positive electrode current collector to be directly electrically connected to the cap assembly.
[0048] Furthermore, the positive electrode material can also be formed by coating a slurry containing a solvent. Examples of the solvent are N-methylpyrrolidone (NMP), cyclohexanone, water, toluene and xylene, but the present disclosure is not limited thereto. Preferably, the solvent for the positive electrode material is NMP. Based on the total weight of the positive electrode material, the amount of the solvent may be, for example, about 10-500 parts by weight. When the amount of the solvent is within the above range, an active material layer can be easily formed, preferably, based on the total weight of the positive electrode material, the amount of the solvent is 40-60 parts by weight.
[0049] The negative electrode is, for example, in sheet form. The negative electrode may include, for example, a negative electrode current collector and a negative electrode material. The negative electrode current collector may, for example, have a thickness of 5 μm to 50 μm. Preferably, the negative electrode current collector is copper foil.
[0050] The negative electrode material is formed on the surface of the negative electrode current collector. The negative electrode material may be formed only on one side of the negative electrode current collector. The negative electrode material may also be formed on both the front and back sides of the negative electrode current collector. The negative electrode material may have a thickness of, for example, 10 μm to 200 μm.
[0051] The negative electrode material may contain, for example, a negative electrode active material. The negative electrode material may also be substantially composed of only a negative electrode active material. The negative electrode active material is selected from graphite (C), soft carbon, hard carbon, silicon-carbon composites, elemental silicon, and SiO x One or more of, preferably graphite (C).
[0052] In a preferred embodiment, the negative electrode comprises a negative electrode current collector made of copper foil and a negative electrode active material layer, wherein the negative electrode active material layer comprises a negative electrode active material coated on both surfaces of the negative electrode current collector as a main component, and the negative electrode active material can be selected from graphite (C), soft carbon, hard carbon, silicon-carbon composite, elemental silicon and SiO x One or more of the above. The negative electrode uncoated portions are formed at both ends of the negative electrode current collector, respectively. The negative electrode uncoated portions are regions where no negative electrode active material layer is formed on one or both surfaces of the negative electrode. The negative electrode tab is equipped on the negative electrode uncoated portion. An insulating tape is wound around a portion of the negative electrode tab extending out of the electrode assembly to prevent a short circuit. The negative electrode tab is electrically connected to the bottom of the housing.
[0053] In a further preferred embodiment, the negative electrode does not include a negative electrode tab, but instead uses an uncoated portion of the negative electrode current collector to be directly electrically connected to the bottom of the housing.
[0054] In addition, a conductive agent and / or a solvent may be optionally included in the negative electrode active material composition and may be the same (or substantially the same) as those described with respect to the positive electrode material composition, and the present invention will not be repeated.
[0055] The ceramic coating is formed by applying a ceramic slurry on at least one surface of the positive electrode and the negative electrode opposite to each other, wherein the ceramic slurry is made by mixing ceramic powder, a binder and a solvent. For example, in a jelly roll electrode assembly formed by stacking and winding two electrodes, a ceramic coating can be formed on at least one surface of the positive electrode and the negative electrode opposite to each other by i) forming a ceramic coating on each outer surface of the two electrodes, or ii) forming a ceramic coating on each inner surface of the two electrodes, or iii) forming a ceramic coating on both the inner and outer surfaces of one of the two electrodes. The ceramic coating can act as a separator, so that a separator made of a polymer such as polypropylene (PP) or polyethylene (PE) can be omitted.
[0056] The ceramic powder includes one or more powders selected from boehmite, alumina, silica, zirconium oxide, zeolite, magnesium oxide, titanium oxide and barium titanate. The decomposition temperature of these materials is higher than 1,000°C, so the thermal stability of the lithium ion battery formed by using the ceramic coating is significantly improved. Since the boehmite material has a plate-like crystal structure, excellent thermal conductivity and excellent flame retardancy. As a preferred, non-limiting example, the ceramic powder is boehmite powder.
[0057] The electrolyte may be, for example, an organic electrolyte. The organic electrolyte is prepared by dissolving a lithium salt in an organic solvent. The organic solvent may be any suitable material that can be used as an organic solvent. Examples of the organic solvent are ethylene carbonate, ethyl vinyl carbonate, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dioxane, 1,2-dimethoxyethane, cyclopentane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or a combination thereof. The lithium salt may be any lithium salt commonly used in the art. For example, the lithium salt is LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x +1SO2)(C y F 2y +1SO2) (wherein x and y are natural numbers), LiCl, LiI or any mixture thereof.
[0058] In addition to the above-mentioned organic electrolytes, other exemplary electrolytes further include non-aqueous electrolytes, organic solid electrolytes, inorganic solid electrolytes, etc. Examples of the organic solid electrolytes include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyester sulfides, polyvinyl alcohol, PVDF, and polymers including ion dissociation groups. Examples of the inorganic solid electrolytes are nitride solid electrolytes, oxynitride solid electrolytes, and sulfide solid electrolytes. Examples of the inorganic solid electrolytes are Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.
[0059] The binder is used to prevent the separation of ceramic powder. As a non-limiting example, the binder can be selected from PVDF, CMC, SBR, polybenzimidazole, polyimide, polyvinyl acetate, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl methylcellulose, regenerated cellulose, polyvinyl pyrrolidone, polyethylene, polypropylene, polystyrene, polymethyl methacrylate, polyaniline, acrylonitrile-butadiene-styrene copolymer, phenolic resin, epoxy resin, polyethylene terephthalate, polytetrafluoroethylene, polyphenylene sulfide, polyamide-imide, polyetherimide, polyethylene sulfone, polyacetal, polyphenylene oxide, polybutylene terephthalate, EPDM, sulfonated EPDM, fluorocarbon rubber and various copolymers, preferably one or more of PVDF, CMC, and SBR. As a preferred, non-limiting example, the binder is PVDF. Generally, when the temperature of the lithium ion battery increases to a temperature exceeding the decomposition temperature of the binder due to an internal short circuit, the binder will burn. Since ceramic powder is an inorganic metal oxide and has heat resistance at a temperature higher than 1,000°C, the amount of ceramic powder is required to be as large as possible, and the binder needs to be used in an amount that maintains the minimum bonding force. The optimal weight ratio of ceramic powder to binder can be changed according to the types of ceramic powder and binder. Preferably, the mass ratio of ceramic powder to binder in the ceramic coating is (80-95):(5-20), preferably (80-90):(10-20), and more preferably 85:15.
[0060] The ceramic powder should be evenly coated without defects to improve the thermal stability of the above-mentioned lithium-ion battery. In other words, the ceramic powder should be coated on the electrode surface with a very uniform thickness without defects such as uncoated parts, small holes and cracks. The present invention has found through a large number of experiments that the above defects can be overcome by controlling factors such as the roughness Ra of the electrode surface, the thickness of the ceramic coating and the particle size of the ceramic powder, thereby obtaining a ceramic coating that can replace the diaphragm.
[0061] As a non-limiting example, the thickness of the ceramic coating is 6 μm to 9 μm, preferably 7 μm to 9 μm, and more preferably 8 μm to 9 μm; the particle size distribution of the ceramic powder satisfies D 50 The roughness Ra of the electrode surface also has a certain influence on the coating effect of the ceramic powder. To meet the coating requirements, as a non-limiting example, the roughness Ra needs to be controlled within a certain range, for example, 0.4 μm to 1.6 μm, preferably 0.6 μm to 1.4 μm, and more preferably 0.8 μm to 1.2 μm.
[0062] In addition, in order to improve the performance of the ceramic coating, such as insulation performance, thermal conductivity, flame retardancy, etc., the ceramic coating may further include an additive. As a non-limiting example, the additive is selected from one or both of PE and PP.
[0063] In order to coat ceramic powder on an electrode active material with a very uniform thickness without defects such as uncoated parts, small holes and cracks, the present invention provides a method for preparing an electrode ceramic coating, comprising the following steps:
[0064] Step 1, measuring the roughness Ra of the electrode surface, if Ra meets the coating requirements, proceed to step 2; if Ra does not meet the coating requirements, pre-treat the electrode surface so that Ra meets the coating requirements;
[0065] Step 2, coating a ceramic slurry on an electrode surface whose roughness Ra meets coating requirements to form a coating layer;
[0066] Step 3, drying the coating layer to obtain a coating.
[0067] Since the roughness of the electrode surface is determined by the surface of the electrode material or the current collector (in the case of uncoated electrode material), if the particle size of the electrode material is small and evenly distributed or the surface of the current collector (in the case of uncoated electrode material) is relatively smooth, the roughness Ra of the electrode surface is small. If the coating requirements are met, the ceramic slurry can be directly coated on its surface to form a coating layer. If the roughness Ra of the electrode surface does not meet the coating requirements, the electrode surface needs to be pretreated. As a non-limiting example, the pretreatment method is to roll the electrode so that Ra meets the coating requirements.
[0068] The ceramic slurry in step 2 includes ceramic powder, a binder and a solvent. The solvent for forming the ceramic slurry may include one or more selected from N-methylpyrrolidone (NMP), cyclohexanone, water, toluene and xylene, and the solvent acts as a dispersion medium to promote the dispersion of the ceramic powder and the binder, and then completely evaporates during the drying process. Thus, the ceramic powder and the binder form a ceramic coating.
[0069] As a non-limiting example, the solid content in the ceramic slurry is 20% to 30%, and the mass ratio of the ceramic powder to the binder is (80 to 95):(5 to 20), preferably (80 to 90):(10 to 20), and more preferably 85:15.
[0070] The method for coating the ceramic slurry in step 2 is a common coating method, including spraying, printing, extrusion or transfer.
[0071] In order to test the performance of the ceramic coating and compare it with the performance of the traditional diaphragm, the Hi-pot test, EIS test, charge and discharge test, cycle life test, heating test and other test methods adopted in the present invention are all conventional testing and characterization means in the field, and the specific operation process will not be repeated in this invention.
[0072] As described above, in the electrode ceramic coating and the lithium ion battery having the electrode ceramic coating, by controlling the roughness of the electrode surface, the thickness of the ceramic coating and the particle size distribution of the ceramic powder, the ceramic powder can be coated on the electrode as a uniform coating without defects such as pinholes and cracks. And the coating can replace the traditional diaphragm, so that the lithium ion battery can be used normally without a diaphragm. And by preventing the current from concentrating in the defective part to prevent the occurrence of internal short circuit, it is possible to prevent the thermal decomposition of the active material and the electrolyte, and the combustion or explosion of the lithium ion battery, which can effectively improve the cycle life of the lithium ion battery. In addition, the ceramic coating is applied with a uniform thickness, and when the electrode column is wound in a jelly roll shape, the electrode column of the desired size can be accurately formed. Specific embodiments
[0074] The following examples describe several embodiments of the present invention and are provided to illustrate the invention but are not intended to limit the invention thereto.
[0075] The method for preparing the electrode ceramic coating used in the following embodiments comprises the following steps:
[0076] Step 1, coating the ceramic slurry on the electrode surface to completely cover the electrode active material (such as NCM or graphite) to form a coating layer;
[0077] Step 2: drying the coating layer at 70° C. to 90° C. to obtain a ceramic coating.
[0078] Wherein, the ceramic slurry is prepared by the following steps:
[0079] Step 1.1, adding a binder (such as PVDF) into a solvent (such as NMP), stirring at a speed of 500 rpm to 700 rpm for 1.5 h to 2.5 h until the binder is completely dissolved in the solvent to obtain a uniform adhesive solution;
[0080] Step 1.2, adding ceramic powder (such as boehmite) to the glue solution obtained in step 1.1, and continuing to stir at a speed of 500 rpm to 700 rpm for 1.5 h to 2.5 h to obtain a uniform ceramic slurry.
[0081] By controlling the added amounts of ceramic powder, binder and solvent, different mass percentages of solid content and different mass ratios of ceramic powder and binder in the ceramic coating can be obtained.
[0082] The calendering process uses the Kejing MSK-2150 calender, the stirring process uses the Kejing MSK-SFM-16 vacuum mixer, and the coating process uses the Kejing MSK-AFA-ES200 coater.
[0083] Example 1: Effect of electrode surface roughness and coating thickness on ceramic coating performance
[0084] (1) Surface roughness measurement and Hi-pot test
[0085] Electrode: The current collector is aluminum foil, the active material is NCM, the original electrode thickness is 140 μm, and the electrode surface is not smooth.
[0086] The above electrodes were pre-calendered and calendered, and the surface roughness was measured. The results are shown in the table below.
[0087]
[0088]
[0089] After the original electrode was pre-rolled from 140 μm to 130 μm, the electrode surface was smooth with a surface roughness Ra of 1.038 μm. The 27% solid content (boehmite to PVDF mass ratio of 85:15, boehmite particle size distribution D 50 A ceramic slurry with a thickness of 0.09 μm) is coated on the electrode surface to form a coating layer, and the coating layer is dried to obtain a ceramic coating, wherein the electrode with a coating thickness of 8 μm can pass the Hi-pot test (the positive electrode sheet with the ceramic coating and the negative electrode sheet without the coating, or the negative electrode sheet with the ceramic coating and the positive electrode sheet without the coating are assembled, and a test voltage of 250 V is applied to test the insulation of the ceramic coating), while the electrode with a coating thickness of 5 μm fails the Hi-pot test.
[0090] After the original electrode was rolled from 140 μm to 104 μm, the surface roughness Ra was 0.398 μm, and some wrinkles appeared on the electrode surface; using 27% solid content (boehmite to PVDF mass ratio of 85:15, boehmite particle size distribution D 50A ceramic slurry with a thickness of 0.09 μm) is coated on the electrode surface to form a coating layer, and the coating layer is dried to obtain a coating layer, and the thickness of the obtained coating layer is uneven.
[0091] (2) EIS test
[0092] Further EIS tests (5mV, 0.1-100KHz) were performed on the original electrode (surface roughness Ra of 1.662μm), the pre-calendered electrode (surface roughness Ra of 1.038μm) and the traditional separator (PE) to obtain the diffusion resistance, diffusion resistivity and capacitance of the symmetrical battery. The results are shown in the table below.
[0093] Original electrode Pre-calendered electrode Diaphragm Coating thickness (μm) 8 8 / Single-side electrode thickness (μm) 56 57 48 <![CDATA[Diffusion resistance (Ω*cm 2 )]]> 4.47 3.30 3.66 Diffusion resistivity(Ω.cm) 798.2 578 762 <![CDATA[Capacitance (mF*cm 2 )]]> 23.5 24 24
[0094] The diffusion resistance and diffusion resistivity of the coated pre-calendered electrode are much smaller than those of the coated original electrode and the traditional diaphragm.
[0095] Example 2: Effect of ceramic materials and particle size distribution on the performance of ceramic coatings
[0096] (1) Hi-pot test
[0097] Electrode: The current collector is aluminum foil and the active material is NCM; the pre-rolled electrode thickness is 130 μm (2.57 g / cc) and the surface roughness Ra is 1.038 μm; the rolled electrode thickness is 104 μm (3.29 g / cc) and the surface roughness Ra is 0.398.
[0098] Ceramic coating: The ceramic material is boehmite, and the particle size distribution of ceramic powder is D 50 They are 0.09μm, 0.4μm, 0.09+2μm (D 50 0.09μm and D 50 2μm, each accounting for 50%), 2μm; or the ceramic material is alumina, the ceramic powder particle size distribution D 50 The thickness of the coating layer is 0.3 μm; a ceramic slurry with a solid content of 27% (the mass ratio of ceramic material to PVDF is 85:15) is applied on the surface of the above-mentioned electrodes to form a coating layer, and the coating layer is dried to obtain a coating. The coating is subjected to a Hi-pot test. The results are shown in the table below.
[0099]
[0100] Among them, the ceramic coatings with a coating thickness of 8μm can all pass the Hi-pot test, while the ceramic coatings with a coating thickness of 5μm all fail. 50 The boehmite ceramic coating with a thickness of 0.09 μm had a partial delamination problem between the rolled electrode and the coating.
[0101] (2) EIS test
[0102] Furthermore, for different particle size distributions of ceramic powders and compared with traditional separators (PE), the diffusion resistance, diffusion resistivity and capacitance of the symmetrical battery were obtained through EIS testing (5mV, 0.1-100K Hz). The results are shown in the table below.
[0103]
[0104] Unexpected discovery, particle size distribution D 50 The diffusion resistance and diffusion resistivity of the boehmite ceramic coating with a particle size of 0.09 μm are much smaller than those of the boehmite / alumina ceramic coatings with other particle size distributions, and even much smaller than those of the traditional diaphragm.
[0105] (3) Pore volume test
[0106] The pore volumes of ceramic coatings with different particle size distributions are compared with the original electrode and the results are shown in the table below.
[0107]
[0108] Among them, the particle size distribution D 50 The pore volume (uL / mL) of the boehmite ceramic coating with a diameter of 0.09 μm is much higher than that of other ceramic coatings and the original electrode.
[0109] Example 3: Effect of Ceramic Coating Composition on Ceramic Coating Performance
[0110] Electrode: The current collector is aluminum foil and the active material is NCM; the original electrode thickness is 140μm (2.36g / cc) and the surface roughness Ra is 1.662μm; the pre-calendered electrode thickness is 130μm (2.57g / cc) and the surface roughness Ra is 1.038μm.
[0111] (1) Effect of solid content in ceramic slurry on the performance of ceramic coating
[0112] Ceramic slurries with different solid contents (mass ratio of boehmite to PVDF is 85:15, particle size of boehmite powder is D 50 The coating layer is dried to obtain a coating having a thickness of 8 μm. The coating is subjected to a Hi-pot test. The results are shown in the following table.
[0113] Solid content (%) 15 20 27 30 35 Viscosity (Cp) 382 1830 18600 87240 181900 Original electrode NG pass pass pass pass Pre-calendered electrode NG pass pass pass pass
[0114] Among them, when the solid content is 15%, it cannot pass the Hi-pot test, and when the solid content is 35%, the viscosity of the ceramic slurry is high and it is difficult to coat on the electrode.
[0115] (2) Effect of the mass ratio of ceramic powder to binder on the performance of ceramic coatings
[0116] A ceramic slurry with a solid content of 27% (the mass ratio of boehmite to PVDF is shown in the table below, and the particle size of the ceramic powder is D 50 The coating layer is dried to obtain a coating having a thickness of 8 μm. The coating is subjected to a Hi-pot test. The results are shown in the following table.
[0117] Boehmite:PVDF 97:3 90:10 85:15 80:20 75:25 Viscosity (Cp) 928 6790 18600 40380 107000 Original electrode NG pass pass pass pass Pre-calendered electrode NG pass pass pass pass
[0118] Among them, when the mass ratio of boehmite to PVDF is 97:3, it cannot pass the Hi-pot test; and when the mass ratio of boehmite to PVDF is 75:25, the viscosity of the ceramic slurry is high and it is difficult to coat on the electrode.
[0119] Example 4: Improvement of the contact angle of the electrode surface by the ceramic coating
[0120] For the different electrodes shown in the table below, the contact angles of the electrode surfaces were measured. The results are shown in Figure 1 .
[0121]
[0122] like Figure 1 As shown, the contact angle of the electrode surface with ceramic coating is smaller than that without ceramic coating, and the electrode with ceramic coating has better wetting effect with electrolyte.
[0123] Example 5 Comparison of performance between ceramic coating and traditional diaphragm
[0124] (1) Charge and discharge test
[0125] The ceramic coating (ceramic material is boehmite, D 50 The full battery without a separator (positive electrode: current collector is aluminum foil, active material is NCM; negative electrode: current collector is copper foil, active material is graphite) is compared with the full battery with a separator (PE). The charge and discharge parameters of the full battery are obtained by charge and discharge test (current is +0.1C / -0.1C, voltage is 4.2-2.5V), see the table below, and the charge and discharge curves are see Figure 2 .
[0126]
[0127] It can be seen that the charge and discharge curves of the boehmite ceramic coating and the separator are basically the same, while D 50 The first efficiency of the 0.09 μm boehmite ceramic coating is slightly higher than that of D 50The boehmite ceramic coating and diaphragm are 0.4μm.
[0128] (2) Cycle life test
[0129] The ceramic coating (ceramic material is boehmite, D 50 The full battery (positive electrode: current collector is aluminum foil, active material is NCM; negative electrode: current collector is copper foil, active material is graphite) without a separator is compared with a full battery containing a separator (PE). The cycle life curve of the full battery is obtained by cycle life test (charging: 6C CC to 4.2V, CV to 0.15C, rest 10min; discharging: 6C DC to 2.5V; rest 10min), see Figure 3 and Figure 4 .
[0130] Unexpectedly, when the number of cycles is ≥400, the average capacity (Ah) of the conventional diaphragm begins to decrease rapidly, while the average capacity of the boehmite coating decreases slowly and is higher than that of the conventional diaphragm. As the number of cycles increases, the gap between the two becomes larger and larger ( Figure 3 As the number of cycles increases, the average capacity rate (%) of the traditional diaphragm begins to decline rapidly. When the number of cycles is ≥450, the average capacity rate of the boehmite coating begins to decline slowly and is higher than that of the traditional diaphragm. As the number of cycles increases, the gap between the two becomes larger and larger ( Figure 4 ).
[0131] Furthermore, the ceramic coating (ceramic material is boehmite, D 50 The full battery (positive electrode: current collector is aluminum foil, active material is NCM; negative electrode: current collector is copper foil, active material is graphite) without a separator is compared with the full battery containing a separator (PE). The cycle life curve of the full battery is obtained by cycle life test (charging: 1C CC to 4.2V, CV to 0.02C, rest 10min; discharging: 1C DC to 2.5V; rest 10min), see Figure 5 and Figure 6 .
[0132] Unexpectedly, when the number of cycles is ≥ 100, D 50 The average capacity (Ah) and average capacity rate (%) of the 0.4μm ceramic coating decreased rapidly, and the average capacity (Ah) and average capacity rate (%) of the traditional diaphragm began to decrease slowly, while D 50The average capacity (Ah) and average capacity rate (%) of the 0.09μm ceramic coating remain basically stable; when the number of cycles is ≥425, the average capacity (Ah) of the boehmite coating is higher than that of the traditional diaphragm. As the number of cycles increases, the gap between the two becomes larger and larger ( Figure 5 ); When the number of cycles is ≥500, the average capacity rate (%) of the boehmite coating is higher than that of the traditional diaphragm. As the number of cycles increases, the gap between the two becomes larger and larger ( Figure 6 ).
[0133] (3) Heating test
[0134] The ceramic coating (ceramic material is boehmite, D 50 The full battery without a separator (positive electrode: current collector is aluminum foil, active material is NCM; negative electrode: current collector is copper foil, active material is graphite) is compared with the full battery with a separator (PE). The heating test curve of the full battery is obtained by heating test (130°C, 100% SOC), see Figure 7 .
[0135] Unexpectedly, the switching voltage of the ceramic coating is lower. After heating at 130°C, the voltage of the conventional diaphragm begins to drop rapidly, while the voltage of the D 50 The voltage of the 0.09 μm boehmite coating remains stable and higher than that of the diaphragm, indicating that the boehmite coating has better thermal stability.
[0136] Example 6 Preparation of a battery without a diaphragm
[0137] The method for preparing a diaphragm-free battery comprises the following steps:
[0138] Step 1, pre-rolling the prepared electrode sheet to make the surface roughness Ra of the electrode sheet 0.8-1.2 μm;
[0139] Step 2, adding the binder PVDF into the solvent NMP, stirring at 600 rpm for 2 h until the PVDF is completely dissolved in the NMP to form a uniform glue solution;
[0140] Step 3, adding the ceramic powder to the glue solution obtained in step 2, and continuing to stir at a speed of 600 rpm for 2 hours to obtain a ceramic slurry;
[0141] Step 4, uniformly coating the prepared ceramic slurry on the surface of the electrode sheet rolled in step 1 to completely cover the active material on the surface of the electrode sheet, and then drying at 80° C. to obtain a ceramic coating, wherein the thickness of the ceramic coating is controlled to be 6 μm to 9 μm, preferably 7 μm to 9 μm, and more preferably 8 μm to 9 μm;
[0142] Step 5, rolling the electrode sheet with ceramic coating obtained in step 4 until the active material reaches the target compaction density (3.4 g / cc for NCM and 1.4 g / cc for graphite);
[0143] Step 6, assembling the electrode plates with ceramic coating obtained in step 4, injecting liquid, and making a battery.
[0144] The above description of various embodiments of the present invention is provided to one of ordinary skill in the relevant art for the purpose of description. It is not intended that the present invention be exclusive or limited to a single disclosed embodiment. As above, a person of ordinary skill in the field of the above teachings will understand the various substitutions and variations of the present invention. Therefore, although some alternative embodiments are specifically described, a person of ordinary skill in the art will understand or relatively easily develop other embodiments. The present invention is intended to include all substitutions, modifications and variations of the present invention described herein, as well as other embodiments that fall within the spirit and scope of the present invention described above.
Claims
1. An electrode ceramic coating, characterized in that: The ceramic coating comprises ceramic powder and a binder, and the particle size of the ceramic powder satisfies D 50 It is 0.05 μm to 0.6 μm, preferably 0.07 μm to 0.4 μm, and more preferably 0.09 μm.
2. The electrode ceramic coating according to claim 1, characterized in that: The ceramic powder material is selected from one or more of boehmite, alumina, silica, zirconia, zeolite, magnesium oxide, titanium oxide and barium titanate, preferably boehmite and alumina, and more preferably boehmite.
3. The electrode ceramic coating according to claim 1, characterized in that: The binder is selected from one or more of PVDF, CMC and SBR, preferably PVDF.
4. The electrode ceramic coating according to claim 1, characterized in that: The mass ratio of ceramic powder to binder in the ceramic coating is (80-95):(5-20), preferably (80-90):(10-20), and more preferably 85:
15.
5. The electrode ceramic coating according to claim 1, characterized in that: The pore volume of the ceramic coating is 280uL / mL to 320uL / mL, preferably 289uL / mL to 316uL / mL, and more preferably 315.7uL / mL.
6. The electrode ceramic coating according to claim 1, characterized in that: The ceramic coating further comprises an auxiliary agent, and the auxiliary agent is selected from one or both of PE and PP.
7. The electrode ceramic coating according to claim 1, characterized in that: The ceramic coating is obtained by coating a ceramic slurry on the electrode surface to form a coating layer, and drying the coating layer.
8. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, an electrolyte and a shell, wherein the positive electrode comprises a positive electrode collector and a positive electrode active material coated on the positive electrode collector, and the negative electrode comprises a negative electrode collector and a negative electrode active material coated on the negative electrode collector; and wherein the positive electrode and the negative electrode are opposite to each other, and at least one surface of the positive electrode and the negative electrode opposite to each other has an electrode ceramic coating as described in any one of claims 1 to 7.
9. The lithium ion battery according to claim 8, characterized in that The positive electrode active material is one or more of lithium nickel cobalt manganese oxide (NCM), lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide (LMO), lithium nickel cobalt aluminum oxide and lithium iron phosphate, preferably lithium nickel cobalt manganese oxide (NCM); the positive electrode current collector is aluminum foil.
10. The lithium ion battery according to claim 8, characterized in that The negative electrode active material is graphite (C), soft carbon, hard carbon, silicon-carbon composite, simple silicon and SiO x One or more of the above, preferably graphite (C); the negative electrode current collector is copper foil.
11. The lithium ion battery according to claim 8, characterized in that The positive electrode and / or the negative electrode further comprises a conductive agent, which may be selected from one or more of conductive carbon black, superconducting carbon black (SP), conductive carbon nanotubes, conductive carbon fibers and graphite-based conductive agents, preferably conductive carbon black, more preferably superconducting carbon black (SP).
12. The lithium ion battery according to claim 8, characterized in that The electrolyte is an organic electrolyte, a non-aqueous electrolyte, an organic solid electrolyte or an inorganic solid electrolyte.
13. The lithium ion battery according to any one of claims 8 to 12, characterized in that: The lithium-ion battery does not include a separator.
14. The lithium ion battery according to any one of claims 8 to 12, characterized in that: The lithium-ion battery does not include tabs.
15. The lithium ion battery according to any one of claims 8 to 12, characterized in that: The compaction density of the positive electrode active material is 2.5 g / cc to 4.0 g / cc, preferably 3.0 g / cc to 3.5 g / cc, and more preferably 3.4 g / cc.
16. The lithium ion battery according to any one of claims 8 to 12, characterized in that: The compaction density of the negative electrode active material is 0.5 g / cc to 2.0 g / cc, preferably 1.0 g / cc to 1.5 g / cc, and more preferably 1.4 g / cc.
17. Use of the electrode ceramic coating according to claim 1 for extending the cycle life of lithium-ion batteries.
18. Use of the electrode ceramic coating according to claim 1 for reducing the average capacity (Ah) decay of lithium-ion batteries after multiple cycles.
19. Use of the electrode ceramic coating according to claim 1 for maintaining the average capacity rate (%) of a lithium-ion battery after multiple cycles.
20. The use according to any one of claims 17 to 19, characterized in that The cycle number of the lithium ion battery is ≥400, preferably ≥500, and more preferably ≥600.
21. The use according to claim 19, characterized in that When the number of cycles of the lithium-ion battery is ≥400, preferably ≥500, and more preferably ≥600, the average capacity rate (%) is maintained at ≥70%, preferably ≥75%, and more preferably ≥80%.
22. Use of the electrode ceramic coating according to any one of claims 1 to 7 for improving the high temperature thermal stability of lithium ion batteries.
23. The use according to claim 22, characterized in that The high temperature is 130° C. or higher.
24. Use of the electrode ceramic coating according to any one of claims 1 to 7 for reducing the contact angle of the electrode surface of a lithium ion battery.